Still standing after all these years: the presence and internet presentation of religious buildings in the Chicago area, 1936–2016. Issue 4 (2nd October 2018) - Miller, Brian J.
Abstract : Scholars have examined the changes in religious architecture over time but few have focused on the ongoing presence of religious buildings in communities nor how long-standing congregations interact with their older building. This study utilises two Internet data sources – Google Street View and the websites of religious congregations – to examine the fate and online presentation of the buildings of four Protestant denominations in the Chicago region from 1936 to today: Disciples of Christ, Lutheran Church-Missouri Synod, Presbyterian, and Seventh-day Adventist. The patterns found show the stability of many church buildings over eight decades and how they help anchor some religious groups – even though newer congregations use a number of these structures – yet congregations make unique choices about presenting their buildings through their website. These findings suggest religious buildings continue to influence their original religious congregations, newer groups using the building and neighbourhoods decades after they are constructed.